IMPLEMENTATION OF FOCUS GROUP DISCUSSION (FGD) BASED INFORMATION SERVICES IN PREVENTING DOMESTIC VIOLENCE - Ica Parhati; Suryati; Putra, Belajanare (Jurnal At-Taujih, 2025)
This study is entitled "Implementation of Information Services Based on Focus Group Discussion (FGD) in Preventing Domestic Violence". Domestic violence (KDRT) is an act of violence committed in the household that can cause suffering, death either physically, psychologically, sexually, economically, deprivation of independence and abandonment in the household. This study aims to determine the application of information services based on focus group discussions (FGD) in preventing domestic violence. This study uses a qualitative approach with a descriptive research method. The subjects in this study were "late teenagers who are married in Sungai Dua Village. The data collection techniques used consisted of three techniques, namely observation, interviews and documentation. The data analysis techniques used in this study were data reduction analysis techniques, data presentation, and drawing conclusions. The results of this study indicate that the community can understand broadly or deeply the knowledge about domestic violence and can control or build awareness of preventing potential violence in the household. The application of information services based on focus group discussions (FGD) was carried out in 4 meetings with a time of 45 / meeting. The implementation of this information service is carried out in 6 stages, namely, the planning stage, the implementation stage, the evaluation stage, the evaluation results analysis stage, follow-up, and reporting.